Karakteristik Kimia, Tensile Strength dan Sensoris Kulit Lumpia dengan Penambahan Tepung Kedelai Hitam. - Dwi Yuliana Astriati; Nurrahman .; Muhammad Yusuf (Universitas Muhammadiyah Semarang, 2022)
Black soybean is a food ingredient that has functional characteristics. Black soybeans have a relationship with health, namely in black soybeans contained anthocyanins and isoflavones. Black soybeans are a source of vegetable protein, each seed contains an average of 37% protein. The addition of black soybean flour to the spring roll skin is intended to increase the nutritional and functional value of the spring roll skin. The purpose of this study was to determine the effect of adding black soybean flour to protein content, antioxidant activity, tensile strength and sensory properties of spring roll skin. The independent variable used was the concentration variation of black soybean flour (0, 2, 4, and 6 percent) with 6 replications. The steps taken were starting with making spring roll skin with the addition of black soybean flour, then analysis was carried out on chemical characteristics (protein content and antioxidant activity), tensile strength and sensory quality (hedonic test and scoring test). The results showed that there was a significant effect of variations in the concentration of black soybean flour on protein content, antioxidant activity, tensile strength and sensory quality of spring roll skin. The conclusion of the research results of spring roll skin with black soybean flour concentration that is 6% concentration is the best treatment with the results of the analysis of protein content: 12.63%, antioxidant activity: 28.95 %RSA, tensile strength: 0.09N/mm2 and taste: 3,37 (somewhat like).